Cellular Oncology - Wang, Cun.; Qiao, Xiaohang; Geurts van Kessel, Ad.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Cellular Oncology publishes scientific contributions from various biomedical and clinical disciplines involved in basic and translational cancer research on the cell and tissue level, technical and bioinformatics developments in this area, and clinical applications. This includes a variety of fields like genome technology, micro-arrays and other high-throughput techniques, genomic instability, SNP, DNA methylation, signaling pathways, DNA organization, (sub)microscopic imaging, proteomics, bioinformatics, functional effects of genomics, drug design and development, molecular diagnostics and targeted cancer therapies, genotype-phenotype interactions. A major goal is to translate the latest developments in these fields from the research laboratory into routine patient management. Cellular Oncology forms a platform of scientific information exchange between molecular biologists and geneticists, technical developers, pathologists, (medical) oncologists and other clinicians involved in the management of cancer patients. Cellular Oncology publishes Original Articles, Reviews, Short Communications, Commentaries, and Letters to the Editor. "In vitro studies are preferentially supported by validations in tumor tissue with clinicopathological associations." .
Keywords: Cancer; Medicine$1 (BResearch.s; Biology$1 (BResearch.s; Pathology; Oncology; Cancer Biology; Biomedical Research; Pathology; Oncology